(untitled) (World Economics and Finance Bulletin, 2024)
This research deals with the mechanism for measuring absolute investment deposit profits for three Jordanian Islamic banks For the period from 2009 to 2023, through this research it was found that there is a statistically significant effect at the level of significance for investment savings deposits on the profitability of Jordanian Islamic banks in the research sample. In addition, there is a statistically significant effect at the level of significance for investment deposits with notification on the profitability of banks, and there is no effect. Statistically significant at the significance level of future investment deposits on banks’ profitability. Accordingly, researchers recommend the need to pay attention to investment savings deposits and deposits with notification because they are of great importance to the bank’s profitability